Growth of Axons - Ciferri, Alberto (Current Chemical Biology, 2016)
The recently elucidated molecular structure of neuronal axons is based on a tubular sequence of adducin-capped actin rings connected by spectrin tetramers. It has been suggested that this structure is formed by supramolecular polymerization of repeating unimers based on spectrin tetramers bound to actin rings. The large number of spectrin molecules connected to each actin ring enormously increases the rigidity of the assembly and the degree of polymerization. During axonal growth, new unimers can dynamically polymerize and macroscopic dimensions are attained. Fundamental self-assembly mechanisms assist the growth of neuronal filaments and coexist with the complex biochemical machinery that assists the biosynthesis and maintenance of the in vivo system.
Keywords: self-assembly